1989
DOI: 10.1101/gad.3.3.265
|View full text |Cite
|
Sign up to set email alerts
|

In vitro formation of short RNA polymerase II transcripts that terminate within the HIV-1 and HIV-2 promoter-proximal downstream regions.

Abstract: Trans-activation of HIV-1 transcription by the viral regulatory protein Tat has been proposed recently to overcome a block to RNA polymerase II elongation in vivo imposed by 5'-untranslated leader sequences. Interestingly, however, only full-length transcripts, rather than prematurely terminated HIV RNAs, are synthesized in most cell-free transcription extracts. Here, we describe an in vitro system in which induction of a highly efficient RNA polymerase II termination or cotranscriptional RNA processing event … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 45 publications
6
89
0
Order By: Relevance
“…The consistency in the lengths of these processed RNAs indicates that transcription preferentially started at the tailed junctions, as previously reported (26). To test that the processing activity was as expected (19,20), we added a pre-RNA (made by SP6 RNA polymerase) corresponding to the full-length transcript of poly(dC)-tailed template 2 and found that the products generated during ongoing transcription (lane 4) corresponded to those obtained [3][4][5] were also labeled by the CCA-end exchange activity in the extract (27). This, however, also served as an internal control for RNA recovery, and lane 6 shows that there are no other products obscured by the strong tRNA signal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The consistency in the lengths of these processed RNAs indicates that transcription preferentially started at the tailed junctions, as previously reported (26). To test that the processing activity was as expected (19,20), we added a pre-RNA (made by SP6 RNA polymerase) corresponding to the full-length transcript of poly(dC)-tailed template 2 and found that the products generated during ongoing transcription (lane 4) corresponded to those obtained [3][4][5] were also labeled by the CCA-end exchange activity in the extract (27). This, however, also served as an internal control for RNA recovery, and lane 6 shows that there are no other products obscured by the strong tRNA signal.…”
Section: Resultsmentioning
confidence: 99%
“…Premature termination (attenuation) in the 5'-proximal regions of several genes in mammalian systems has been examined by either promoter-directed transcription in cell extract systems (4-10) or promoterless transcription with purified pol II (11-14). These sites may be intrinsic terminators for pol II and contain distinct signals such as RNA stem-loop structures (5,7,14), DNA bending in T-rich tracts (13), or other, structureless sequences (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4C) is based on the observation that prematurely terminated HIV RNAs are stable (31,34). The TM RNase protection bands represent a diffuse set of RNAs with 3Ј ends in the HIV-2 TAR sequence, which acts as a terminator and/or stabilizer of terminated transcripts (66). The RT RNase protection product represents transcripts which initiate correctly and extend beyond position Ï©165.…”
Section: To 4)mentioning
confidence: 99%
“…The general transcription factors IIF and UX were also shown to alleviate this block to transcription elongation. On the basis of these results, we suggest that the block to elongation at the MVM attenuation site observed late in MVM infection results, at least in part, from the inactivation of the general transcription elongation factors.Recently, it has been shown that eukaryotic RNA polymerase II, like the prokaryotic polymerase, can pause or terminate both in vivo and in vitro transcription within viral (1,3,16,17,19,24,28,29,32,38) and cellular (4,8,9,15,18) genes and thus modulate downstream gene expression. This mechanism is termed attenuation (39).…”
mentioning
confidence: 99%